Effects of calorie restriction on the lifespan and healthspan of POLG mitochondrial mutator mice. - Shinichi Someya; Gregory C Kujoth; Mi-Jung Kim; Timothy A Hacker; Marc Vermulst; Richard Weindruch; Tomas A Prolla (PLoS ONE)
Mitochondrial DNA (mtDNA) mutations are thought to have a causative role in age-related pathologies. We have shown previously that mitochondrial mutator mice (PolgD257A/D257A), harboring a proofreading-deficient version of the mtDNA polymerase gamma (POLG), accumulate mtDNA mutations in multiple tissues and display several features of accelerated aging. Calorie restriction (CR) is known to delay the onset of age-related diseases and to extend the lifespan of a variety of species, including rodents. In the current study we investigated the effects of CR on the lifespan and healthspan of mitochondrial mutator mice. Long-term CR did not increase the median or maximum lifespan of PolgD257A/D257A mice. Furthermore, CR did not reduce mtDNA deletions in the heart and muscle, accelerated sarcopenia, testicular atrophy, nor improve the alterations in cardiac parameters that are present in aged mitochondrial mutator mice. Therefore, our findings suggest that accumulation of mtDNA mutations may interfere with the beneficial action of CR in aging retardation.